Students’ Knowledge Level Towards Generation Planning Program in the city of Banda Aceh - Safrizan, Safrizan; Mawarpury, Marty; Sofia, Sofia; Usman, Said; Sahputra, Irwan (STRADA : Jurnal Ilmiah Kesehatan, 2021)
The GenRe program in Banda Aceh has been running since 2015, but in its implementation only 7 out of 47 SMA / SMK in Banda Aceh City have actively participated in the GenRe program. This information was obtained from the researchers’ initial interviews with the PIK R / M extension team in Banda Aceh, stating that there were many obstacles in implementing the GenRe program in Banda Aceh, such as the lack of youth participation in attending counseling, limited human resources (HR). This study used a descriptive quantitative approach involving 377 students spread across 14 SMA / MA / SMK in Banda Aceh City. The results showed that of 377 students in Banda Aceh 46.9% did not know the GenRe program, 79.8% had not attended the GenRe program with the PIK R / M container and 58% had good knowledge about reproductive health